Hubungan Pengetahuan Ibu dengan Pemilihan Metode Kontrasepsi Jangka Panjang (MKJP) - Dyan Oktaviany; Alisya Rahza Fithri (An-Najat, 2024)
The participation or involvement of family planning acceptors in the selection and use of long-acting contraceptive methods (LACMs) in Indonesia is still relatively low. The factors contributing to the minimal participation of KB acceptors in the selection or use of LACMs include the low level of knowledge among acceptors regarding the use of LACMs. To explain the relationship between KB acceptors’ knowledge and the selection of LACMs. This literature review used a systematic literature review of 10 articles related to the topic, which have been screened. The researcher found that there is a relationship between knowledge and the selection of LACMs. According to the researcher and the data obtained, it can be concluded that there is a match between the researcher’s literature review results and current theory, as well as previous research results